Atomic and R-functions in radiophysical applications - Kravchenko, V. F. (Видавництво Національного університету "Львівська політехніка", 2009)
This review consist of two parts. First part of review concerned with atomic functions theory and it’s applications in digital signal processing problems, antennas synthesis and sampling theorem. In second part R-functions theory and WA-system functions are considered in applications to boundary-value problems of elliptic type.
Keywords: Atomic and R-functions; synthesis; analysis; WA-system functions